Lifestyle Differences of Muhammadiyah and NU Adolescents in Semarang: A Social Interpretation toward SDGs - Saka Mahardika Oktav Nugraha; Juhadi; Hamdan Tri Atmaja; Nugraha Trisnu Brata; Hanip Hidayatulloh (Universitas Muhammadiyah Surakarta, 2025)
Objective: This study explores the social interpretation of lifestyle differences between Muhammadiyah and Nahdlatul Ulama (NU) adolescents in Semarang City within the framework of achieving the Sustainable Development Goals (SDGs), particularly Goal 4 (Quality Education), Goal 10 (Reduced Inequalities), and Goal 16 (Peace, Justice, and Strong Institutions). Theoretical framework: The theoretical framework is grounded in social construction theory and religious sociology, examining how social and religious identities shape behavior. Literature review: The literature review emphasizes previous research on Islamic youth subcultures, lifestyle studies, and the role of religious institutions in shaping adolescent identity. Methods: This study employs a qualitative method using a phenomenological approach to deeply understand the lived experiences and perceptions of youth from both Muhammadiyah and NU backgrounds. Data were collected through in-depth interviews with members of both youth communities and participant observation. The study also includes an analysis of a recent conflict arising from differing views on worship practices. Results: The findings reveal two main points. First, ideological differences have led to disagreements in social interpretations of worship behavior. Second, lifestyle disparities emerge in clothing preferences and consumption patterns, reflecting deeper cultural and theological differences. These differences pose communication barriers between the two communities. However, the research also finds that mosque-based youth programs can serve as a communication bridge, promoting synergy and mutual understanding through structured, one-way interpretation communication models. Implications: The implications of this research highlight the need for inclusive religious education models and inter-community dialogue as tools to support SDG values such as tolerance, equality, and social harmony. Novelty: The novelty of the study lies in its contextual focus on youth identity formation within religious organizations and its integration of the SDGs perspective into the analysis of intra-religious diversity in urban Islamic settings.